2020
DOI: 10.1096/fj.202000912rr
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complex of the lysosomal membrane transporter MFSD1 and its accessory subunit GLMP

Abstract: The major function of lysosomes is the hydrolytic breakdown of various macromolecules including proteins, lipids, nucleic acids, and oligosaccharides, to low-molecular-weight metabolites which can be re-used in the cytosol for biosynthetic pathways. 1 The resulting low-molecular-weight degradation products are exported via the limiting lysosomal membrane to the cytosol by the action of numerous transporter proteins, of which many are still enigmatic. 2 Some transporter proteins actively import a subset of meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The cloning of MFSD1-eGFP was described previously [8]. GLMP-HA was PCR amplified from pcDNA3.1-GLMP-HA [11] with forward primer 5'-GGGGACAAGTTTGTACAAAAAAGCAGGCTTAATGTTTCGCTGTTGG-3' and reverse primer 5'-GGGGACCACTTTGTACAAGAAAGCTGGGTATTAAGCGTAGTCTGGGAC-3'.…”
Section: Recombinant Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cloning of MFSD1-eGFP was described previously [8]. GLMP-HA was PCR amplified from pcDNA3.1-GLMP-HA [11] with forward primer 5'-GGGGACAAGTTTGTACAAAAAAGCAGGCTTAATGTTTCGCTGTTGG-3' and reverse primer 5'-GGGGACCACTTTGTACAAGAAAGCTGGGTATTAAGCGTAGTCTGGGAC-3'.…”
Section: Recombinant Proteinsmentioning
confidence: 99%
“…MFSD1 was initially identified as a lysosomal membrane protein [9], and was additionally shown to be required for normal tissue physiology [10], as MFSD1 -/mice develop splenomegaly and severe liver disease. MFSD1's stability in lysosomes depends on its interaction with Glycosylated Lysosomal Membrane Protein (GLMP) [9,11]. Even these few examples show that MFSD1 is crucial for normal physiology, however its cellular and molecular functions remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, all these proteins have one thing in common: They all have highly N‐glycosylated accessory subunits, with which they closely interact, and which presumably takes over the protective function. CLC‐7 is tightly linked to the highly N‐glycosylated type I transmembrane protein OSTM1 [61], ABCB9 interacts with LAMP1 and LAMP2 [65], MFSD1 interacts with the highly N‐glycosylated type I transmembrane protein GLMP [64,66], and ABCD4 is interacting with LMBD1 [67–69]. In all cases, these accessory proteins seem to share at least their role in protecting the transporter from degradation (Fig.…”
Section: Transporter—accessory Protein Complexes Are Common Features Of Lysosomal Membrane Proteinsmentioning
confidence: 99%
“…However, these accessory subunits take over additional functions beyond protection: They often additionally mediate or influence the sorting of the complexes from the ER and the Golgi to lysosomes and in some cases directly affect the transporting capacity, for example, in the case of the Cl(‐)/H(+) exchanger CLC‐7 [70,72]. Similarly, we have shown that GLMP affects the trafficking of MFSD1 [66]. Stabilizing ‘chaperoning’ functions of accessory subunits beyond providing an ‘N‐glycan shield’ are additionally supported by a couple in which both partners are N‐glycosylated, excluding the essential need for protective function: ATRAID and SLC37A3, which both together form a transporter complex for the cytosolic entry of nitrogen‐containing bisphosphonates from the lysosomal lumen to the cytosol [55].…”
Section: Transporter—accessory Protein Complexes Are Common Features Of Lysosomal Membrane Proteinsmentioning
confidence: 99%
“…MFSD1 was initially identified as a lysosomal membrane protein ( 9 ) and was additionally shown to be required for normal tissue physiology ( 10 ), as MFSD1 −/− mice develop splenomegaly and severe liver disease. The stability of MFSD1 in lysosomes depends on its interaction with Glycosylated Lysosomal Membrane Protein (GLMP) ( 9 , 11 ). Even these few examples show that MFSD1 is crucial for normal physiology; however, its cellular and molecular functions remain unknown.…”
Section: Introductionmentioning
confidence: 99%